On the formation of molecules and solid-state compounds from the AGB to the PN phases. Issue 3 (July 2016) - García-Hernández, D. A.; Manchado, A.
Abstract: During the asymptoyic giant branch (AGB) phase, different elements are dredge- up to the stellar surface depending on progenitor mass and metallicity. When the mass loss increases at the end of the AGB, a circumstellar dust shell is formed, where different (C-rich or O-rich) molecules and solid-state compounds are formed. These are further processed in the transition phase between AGB stars and planetary nebulae (PNe) to create more complex organic molecules and inorganic solid-state compounds (e.g., polycyclic aromatic hydrocarbons, fullerenes, and graphene precursors in C-rich environments and oxides and crystalline silicates in O-rich ones). We present an observational review of the different molecules and solid-state materials that are formed from the AGB to the PN phases. We focus on the formation routes of complex fullerene (and fullerene-based) molecules as well as on the level of dust processing depending on metallicity.